The Effect of Islamic Financial Literacy and Financial Inclusion toward Financial Planning among Millennial: Financial Behaviour as an Intervening Variable - Lusiana Handayani; Basyirah Ainun; M. Yassir Fahmi (International Journal of Emerging Issues in Islamic Studies, 2021)
Islamic financial literacy and financial inclusion are important for improving the living condition of people. Combination of Islamic financial literacy understanding and high financial inclusion index will affect the behavioral ability of people in making financial planning. In Indonesia, Islamic financial literacy and inclusion are still low, not only for youngsters but also among adults. Even though good knowledge and access to Islamic finance will help millennials to be able to identify financial products and services as their financial planning. The aim of this study is to describe the influence of Islamic financial literacy and financial inclusion on financial planning by using financial behaviour as a intervening variable. This study is descriptive quantitative research. 96 respondents are involved in the study directly through a survey method. This study used 2 (two) stages of analysis. The first stage is to find the level of respondent Islamic financial literacy. The last stage is path analysis to determine the influence of each variable. Analysis results have shown that Islamic financial literacy has no direct impact on financial planning. However, Islamic financial literacy and financial inclusion have a significant impact on financial behaviour. Furthermore, the financial behaviour has mediated the relationship between Islamic financial literacy and financial inclusion with financial planning. It shows this affects toward financial planning is 26,4%.